PELAKSANAAN MONITORING KEPALA CABANG TERHADAP PELAYANAN KARYAWAN BMT UGT KANIGARAN PROBOLINGGO - Badrut Tamam; M. Munir (IZZI: Jurnal Ekonomi Islam, 2024)
This study aims to determine the implementation process of Branch Head Monitoring of BMT-UGT Kanigaran Employee Services in Probolinggo City. This research uses qualitative methods, the collection technique is through active observation, interviews with branch heads and BMT-UGT Sidogiri employees. This intends to find out the state of something about what and how, and so on. the results of the study, it was found that the Implementation of the Monitoring Task by the Branch Manager towards the Service of BMT-UGT Kanigaran Employees of Probolinggo City, is to use Sidak, or unscheduled according to the wishes of the Branch Manager.